Histology of human teeth: Standard and specific staining methods revisited. (July 2021) - Widbiller, M.; Rothmaier, C.; Saliter, D.; Wölflick, M.; Rosendahl, A.; Buchalla, W.; Schmalz, G.; Spruss, T.; Galler, K.M.
Highlights: Histological techniques provide indispensable contributions in dental research. Gravimetry and radiography are suitable for monitoring the decalcification process. Staining techniques need to be optimized for dental tissues. Light-, polarization- and fluorescence microscopy provide insights in tooth structure. Abstract: Objective: Histological techniques have long been an integral part of dental research. Especially the processing of complex tissues poses specific challenges, however, literature offers only few technical references. Objectives of this study were therefore to optimize histological staining methods and compile detailed protocols for preparation and staining of dental tissues. Methods: Human teeth were collected and fixed with 4 % formaldehyde solution after extraction. Subsequently, teeth were decalcified in 17 % EDTA or Morse's solution over a period of 28 days. The extent of decalcification was determined by weight loss and radiography. After sectioning, histological staining methods were optimized for their use on teeth. These included hematoxylin-eosin, Masson trichrome, Masson-Goldner trichrome and May-Gruenwald-Giemsa staining. Nerve fibres were visualized by luxol fast blue staining and Bodian silver staining. In addition, specific methods like TRAP, modified Brown and Brenn as well as picrosirius red staining with light polarization or fluorescence were applied and optimized. Results: Preparation of an artificial access to the pulp chamber was essential to ensure prompt penetration of the chemicals. Decalcification with Morse's solution took at least two weeks but was more efficient than 17 % ETDA, where thorough demineralization was achieved only after three weeks. The staining methods exhibited differences not only regarding their ability to display specific structures of interest, but also in terms of reproducibility. Conclusion: High-quality histology of teeth can only be achieved after optimal tissue preparation and accurate staining. A complementary use of staining techniques is necessary to answer specific research questions.